The Role of Continuous Positive Airway Pressure Therapy in the Management of Respiratory Distress in Extremely Premature Infants - Sekar, Kris (Pediatric Pharmacy Advocacy Group, 2006)
The use of mechanical ventilation for the treatment of respiratory distress syndrome (RDS) in low birth weight infants may cause barotrauma, volutrauma, and chronic lung disease. Different continuous positive airway pressure (CPAP) delivery systems exist, each with its own practical and clinical advantages and disadvantages. CPAP can be used as either a primary or an adjunctive respiratory support for RDS. Research demonstrates that CPAP decreases the incidence of respiratory failure after extubation. Clinical trials indicate that the optimal management of neonatal RDS consists of early surfactant treatment followed quickly by extubation and stabilization on CPAP. Early surfactant treatment combined with CPAP reduces the need for mechanical ventilation, compared to later surfactant treatment. Evidence suggests a synergistic effect between early surfactant administration and rapid extubation to nasal CPAP.